Transmission of financial shocks in loan and deposit markets: Role of interbank borrowing and market monitoring - Allen, Franklin; Hryckiewicz, Aneta; Kowalewski, Oskar; Tümer-Alkan, Günseli (Journal of Financial Stability, 2014)
We examine the international transmission of liquidity shocks from multinational bank holding companies to their subsidiaries during the financial crisis of 2008. Our results demonstrate that a subsidiary's reduction in lending is strongly related to its parent bank's lending via the interbank market. While subsidiaries that were dependent on interbank financing increased their credit supply prior to the crisis, they reduced their lending activities during the crisis. Additionally, we observe that interbank-dependent subsidiaries tried to change their funding strategy when they were unable to increase their deposit growth significantly during the crisis. During the crisis, subsidiaries could not rely on their parent banks’ support via the interbank market and encountered problems in attracting new depositors, which could explain the significant decline in lending during the financial crisis. These findings highlight the need to regulate and monitor multinational funding strategies, especially in the interbank market.